Development of an EGMA-Based E-Booklet Numeracy Assessment Instrument for Phase B Students in Elementary School - Bagus Santoso; Gunawan Gunawan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aimed to develop an e-booklet numeracy assessment instrument based on the Early Grade Mathematics Assessment (EGMA) that meets the criteria of validity and practicality for Phase B elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants included two expert validators, eight Grade III and IV teachers, and 45 Phase B students. Data were collected through expert validation sheets, teacher and student response questionnaires, and students’ performance on the numeracy assessment instrument. Data were analyzed using descriptive quantitative analysis based on percentage scores to determine the validity and practicality of the product, while students’ performance results were used to map numeracy achievement across the assessed domains. The results showed that the EGMA-based e-booklet numeracy assessment instrument achieved a validity percentage of 85.00% and met the valid criteria. User responses indicated that the instrument achieved a practicality percentage of 88.54% from teachers and 89.48% from students. The assessment results also indicated variations in achievement across the numeracy domains, with basic numeracy demonstrating the highest achievement and numeracy problem solving demonstrating the lowest. The developed instrument has the potential to serve as an alternative formative assessment tool for mapping Phase B students’ numeracy abilities in a more structured, contextualized, and easily implementable manner through digital media